The EU and Africa in the XXIst Century: Time for a New Deal - (:unkn) unknown (My University, 2013)
The Cotonou Partnership Agreement (CPA) was launched nearly a decade and a half ago, yet the pending negotiations of economic partnership agreements (EPAs) between the European Union (EU) and the African, Caribbean and Pacific (ACP) countries and regions still show no sign of significant progress in most cases. The issue has been a bone of contention in EU-Africa relations and is about to become a textbook illustration of Europe's limited ability to impose its views, a sharp contrast with the post-cold war decade. Brussels seems to be belatedly discovering that African states have recovered margins of negotiation, an unprecedented situation since the early 1970s. Against such a backstage, the Brussels EU-Africa Summit of April 2014, will find it difficult to convince Africans that the 'strategic partnership' launched in 2007 is more than a placebo. The Summit may be conceived as a mere exercise in public diplomacy, but in such a case the 'aura' of the EU is likely to be dimmed by demonstrations and public protests, as was the case during the Lisbon summit of 2007. It is therefore high time for the EU to operate a Copernician revolution. This should involve the definition of a more pragmatic set of priorities, based on the identification of what European interests are (or could be) in Africa, and a departure from the assumption that sub-Saharan Africa is still Europe's backyard.
Keywords: African Research